2021
DOI: 10.1186/s40575-021-00110-5
|View full text |Cite
|
Sign up to set email alerts
|

Heritability of distichiasis in Havanese dogs in Norway

Abstract: Background Distichiasis is a presumed inherited eyelid disease, characterized by misplaced eyelashes. The effect on eye health and animal welfare varies between individuals; most mild cases show no clinical signs, but some affected animals develop painful corneal disease. In this study, we investigated the prevalence and heritability of distichiasis in the Norwegian population of Havanese dogs. Results A total of 1156 Havanese were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 9 publications
0
6
1
Order By: Relevance
“…The estimated heritability of h 2 pedO = ~ 0.22 and h 2 pedT ~ 0.48 on the underlying scale agrees with other studies of dogs [ 8 , 10 ], even if there is some variation between breeds. While Ketteritzsch estimated a lower heritability in Tibetan terriers [ 9 ], our estimated pedigree-based heritability is slightly lower than in the study of Bellamy et al [ 16 ].…”
Section: Discussioncontrasting
confidence: 86%
See 3 more Smart Citations
“…The estimated heritability of h 2 pedO = ~ 0.22 and h 2 pedT ~ 0.48 on the underlying scale agrees with other studies of dogs [ 8 , 10 ], even if there is some variation between breeds. While Ketteritzsch estimated a lower heritability in Tibetan terriers [ 9 ], our estimated pedigree-based heritability is slightly lower than in the study of Bellamy et al [ 16 ].…”
Section: Discussioncontrasting
confidence: 86%
“…Due to the low prevalence and limited predictive value in the youngest age groups, the pedigree-based heritability estimates were based on dogs examined after 52 weeks. We based our estimates on a linear model, as Bellamy et al showed a good agreement between heritability estimates from the Bayesian threshold model and heritability from linear models converted to the underlying scale [ 16 ]. The estimated heritability of h 2 pedO = ~ 0.22 and h 2 pedT ~ 0.48 on the underlying scale agrees with other studies of dogs [ 8 , 10 ], even if there is some variation between breeds.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4 It is considered an inherited condition, but the mode of inheritance remains unknown. [4][5][6][7][8][9] These aberrant hairs may cause ocular discomfort and ocular surface alterations, such as ulcerative or non-ulcerative keratitis. 2,3 To date, there have been no reports on the prevalence of the clinical signs associated with distichiasis in dogs.…”
Section: Introductionmentioning
confidence: 99%